Strategi Komunikasi Komunitas Pusat Kajian Perempuan Solo (PUKAPS) dalam Menyuarakan Isu Gender dan Kekerasan Seksual - Ulfa Fauzia Argestya; Anisa Rohmah Afiati (UIN Raden Mas Said Surakarta, 2022)
The Solo Women's Study Center (PUKAPS) community which actively discusses issues of gender equality and feminist discourse and accepts complaint space for survivors of sexual violence, especially in the city of Surakarta. This study aims to determine the communication strategies used in the Pukaps Community in voicing issues of gender and sexual violence so that people become more sensitive to the existing reality. This study uses a qualitative approach with the method of descriptive analysis. Data collection techniques were carried out through direct interviews with three division heads from the Pukaps Community. The results of this research show that there is a communicator selection strategy based on the credibility, background and attractiveness of the communicator. the strategy for compiling and presenting messages is formulated in an informative, educative and persuasive manner in Pukaps social media content. The media selection strategy uses Pukaps social media, both Instagram, Facebook and media zoom meetings for webinar activities. The strategy for selecting and identifying audiences is in the form of observing the general public in order to see if the education carried out by the Pukaps Community is on target or not. All efforts in the communication strategy carried out by the Pukaps community seek to provide significant and routine information to the general public, especially the people of the city of Solo regarding current gender issues and sexual violence.